2008
DOI: 10.1016/j.marchem.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Air–water exchange of polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) at a coastal site in Izmir Bay, Turkey

Abstract: The air-water exchange of polychlorinated biphenyl (PCB) and organochlorine pesticides (OCPs) were investigated using paired air-water samples (n = 16) collected in July and February-March, 2005 from Guzelyali Port in Izmir Bay, Turkey. Atmospheric PCBs and OCPs were mainly in gas-phase in both periods. However, their dissolved and particle-phase water concentrations were comparable. For PCBs, 3 and 4-Cl congeners were dominant while chlorpyrifos, endosulfans and HCHs were the most abundant OCPs for all sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 49 publications
2
42
1
1
Order By: Relevance
“…Compounds were identified based on their retention times and target and qualifier ions, and were quantified using the internal standard calibration procedure. Additional details can be found elsewhere for PCBs, OCPs (Sofuoglu et al 2004;Odabasi et al 2008), and PAHs (Demircioglu et al 2011 Average recoveries (determined from the response ratios from calibration and sample analysis runs) of PCB surrogate standards including filters and PUFs were 97 ± 17 % for PCB-14, 107 ± 18 % for PCB-65, and 93 ± 31 % for PCB-166 (n = 102). The recoveries of target compounds were also determined externally by matrix spike experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds were identified based on their retention times and target and qualifier ions, and were quantified using the internal standard calibration procedure. Additional details can be found elsewhere for PCBs, OCPs (Sofuoglu et al 2004;Odabasi et al 2008), and PAHs (Demircioglu et al 2011 Average recoveries (determined from the response ratios from calibration and sample analysis runs) of PCB surrogate standards including filters and PUFs were 97 ± 17 % for PCB-14, 107 ± 18 % for PCB-65, and 93 ± 31 % for PCB-166 (n = 102). The recoveries of target compounds were also determined externally by matrix spike experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Sample quantities exceeding the MDLs were quantified and blank-corrected by subtracting the mean blank amount from the sample amount. Additional QA/QC information can be found in Sofuoglu et al (2004), Odabasi et al (2008), and Demircioglu et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Theoretically, where f a /f w = 1 at air-water equilibrium, f a /f w > 1 indicates net deposition from air to water, and f a /f w b 1 indicates net volatilization from the water. Although H values have been done for salinity and temperature corrections, the overall uncertainty of H value still existed (Bruhn et al, 2003;Odabasi et al, 2008). While it is not possible to obtain an objective measure of this uncertainty, recommended value of 30% for uncertainty might be appropriate, based on the results of previous evaluations, different laboratory artifacts and the uncertainties in the air and water-side mass transfer coefficients (Bruhn et al, 2003;Odabasi et al, 2008).…”
Section: Air-water Gas Exchange Of Selected Ocpsmentioning
confidence: 99%
“…Studies on gas and particle phase concentrations of atmospheric PCBs in urban/industrial sites of Bursa suggested that local sources and long range atmospheric transport mainly contributes to PCB pollution in this region with lower chlorinated PCB congeners dominating the samples [58 -61]. Cetin et al [46] and Odabasi et al [57] measured PCB concentrations in the Izmir atmosphere and stated that the observed concentrations were within the range of values reported previously for urban and industrialized areas in the literature. Cetin et al [46] noted that summer concentrations of PCBs were higher than those in winter in the industrial site studied.…”
Section: Pcbs In Airmentioning
confidence: 61%
“…Cetin et al [46] noted that summer concentrations of PCBs were higher than those in winter in the industrial site studied. Similarly, Odabasi et al [57] stated that the net gas exchange PCB fluxes from an urban site, namely Güzelyali Port in Izmir, was mainly volatilization (especially of tri and tetra-chlorobiphenyls) in summer and deposition in winter.…”
Section: Pcbs In Airmentioning
confidence: 98%